On the hyperbolic type differential equation with time involution - Ashyralyev, A.; Ashyralyyev, A.; Abdalmohammed, B. (Bulletin of the Karaganda University. Mathematics Series, 2023)
In the present paper, the initial value problem for the hyperbolic type involutory in t second order linear partial differential equation is studied. The initial value problem for the fourth order partial differential equations equivalent to this problem is obtained. The stability estimates for the solution and its first and second order derivatives of this problem are established.